Multiplicities and Dimensions in Enveloping Tensor Categories - Knop, Friedrich (International Mathematics Research Notices, 2024)
In a previous paper, semisimple tensor categories were constructed from certain regular Mal’cev categories. In this paper, we calculate the tensor product multiplicities and the categorical dimensions of the simple objects. This yields also the Grothendieck ring. The main tool is the subquotient decomposition of the generating objects.
CRIS-Team Scopus Importer:2024-05-24